International Monetary Fund Annual Report 1977. (Annual Report of the Executive Board; Annual Report of the Executive Board ;, 1977)
This paper reviews key findings of the IMF's Annual Report for the fiscal year ended April 30, 1977. The report highlights that after a cessation of economic growth in 1974 and an unusual decline in 1975, real gross national product in the industrial countries expanded by almost 5 1\2 percent in 1976. Increases in the range of 5-6 1\2 percent occurred in all of the larger industrial countries except the United Kingdom. The deep and prolonged international recession that started late in 1973 reached its low point in the first half of 1975.